Survival and recurrent venous thromboembolism in patients with first proximal or isolated distal deep vein thrombosis and no pulmonary embolism. (24th May 2017) - Barco, S.; Corti, M.; Trinchero, A.; Picchi, C.; Ambaglio, C.; Konstantinides, S. V.; Dentali, F.; Barone, M.
Abstract : Essentials The long‐term risk of recurrence and death after distal deep vein thrombosis (DVT) is uncertain. We included subjects with first proximal or isolated distal DVT (IDDVT) and no pulmonary embolism. The risk of symptomatic and asymptomatic recurrence is lower after IDDVT (vs. proximal). IDDVT may be associated with a lower long‐term risk of death, especially after unprovoked DVT. Summary: Background: A few studies have focused on the risk of recurrence after first acute isolated distal deep vein thrombosis (IDDVT) compared with proximal DVT (PDVT), whereas the incremental risk of death has never been explored beyond the first 3 years after acute event. Methods: Our single‐center cohort study included patients with first symptomatic acute PDVT or IDDVT. Patients were excluded if they had concomitant pulmonary embolism (PE) or prior venous thromboembolism. The primary outcomes were symptomatic objectively diagnosed recurrent PDVT or PE and all‐cause death. Results: In total, 4759 records were screened and 831 subjects included: 202 had symptomatic IDDVT and 629 had PDVT. The median age was 66 years and 50.5% were women. A total of 125 patients had recurrent PDVT or PE during 3175 patient‐years of follow‐up: 109 events occurred after PDVT (17.3%) and 16 after IDDVT (7.9%). Annual recurrence rates were 4.5% (95% confidence interval [CI], 3.7–5.4%) and 2.0% (95% CI, 1.1–3.2%), respectively, for an adjusted hazard ratio (aHR) for IDDVT patients of 0.32 (95% CI, 0.19–0.55). Death occurred in 263 patients (31.6%[ 95% CI, 28.6–34.9%]) during 5469 patient‐years of follow‐up for an overall annual incidence rate of 4.8% (95% CI, 4.2–5.4%). The mortality rate was 33.5% ( n = 211) in PDVT patients and 25.7% ( n = 52) in IDDVT patients. The long‐term hazard of death appeared lower for IDDVT patients (aHR, 0.75 [95% CI, 0.55–1.02]), especially after unprovoked events (aHR, 0.58 [95% CI, 0.26–1.31]). Conclusions: Compared with PDVT, IDDVT patients were at a lower risk of recurrent VTE. The risk of death appeared lower after IDDVT during a median follow‐up of 7.6 years.